Formation of differential rotation in a cylindrical fluid layer - Sukhanovsky, Andrey Nikolaevich (Computational Continuum Mechanics, 2010)
The formation of differential rotation observed in a rotating cylindrical layer heated locally is considered. Simulations have been done for different values of control parameters such as the geometry of a model (layer height, radius and heating area), the kinematic viscosity, the heat flux and the angular velocity of a cylinder. The integral characteristics of differential rotation are presented. The dependence of the relative angular momentum of the layer on different parameters has been studied.